2021
DOI: 10.1037/apl0000947
|View full text |Cite
|
Sign up to set email alerts
|

Getting worse or getting better? Understanding the antecedents and consequences of emotion profile transitions during COVID-19-induced organizational crisis.

Abstract: While some organizations are thriving during the COVID-19 pandemic, many are experiencing a crisis—a threat to organizational longevity, time pressure, and inadequate resources. Building on prior work examining emotions during times of crisis and changes that people undergo during major life transitions, as well as media accounts suggesting that employees have had positive and negative emotions tied to aspects of working during COVID-19, we adopt a person-centric view to examine profiles of monthly emotions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 105 publications
1
42
0
1
Order By: Relevance
“…Research also investigated organizational factors, in particular, leader behaviors, that impacted employees' feelings during the pandemic crisis. In this vein, Slaughter et al (2021) found that perceived leader trustworthiness and effective handling of the pandemic in the work context were critical factors that supported employees to shift from negative to more positive emotional profiles during the crisis, indicated by higher levels of hope and gratitude, as well as reduced feelings of fear and resentment. In sum, this initial evidence indicates that exogenous crises, such as the COVID‐19 pandemic, will likely impact how individuals feel when at work and that leaders may help attenuate negative influences on employee emotions in this context.…”
Section: Setting the Scene: What Have We Learned About Organizational...mentioning
confidence: 99%
“…Research also investigated organizational factors, in particular, leader behaviors, that impacted employees' feelings during the pandemic crisis. In this vein, Slaughter et al (2021) found that perceived leader trustworthiness and effective handling of the pandemic in the work context were critical factors that supported employees to shift from negative to more positive emotional profiles during the crisis, indicated by higher levels of hope and gratitude, as well as reduced feelings of fear and resentment. In sum, this initial evidence indicates that exogenous crises, such as the COVID‐19 pandemic, will likely impact how individuals feel when at work and that leaders may help attenuate negative influences on employee emotions in this context.…”
Section: Setting the Scene: What Have We Learned About Organizational...mentioning
confidence: 99%
“…Indeed, even within attribution theories, although it is inferred that attributions should combine (e.g., Eid, 2001;Moors, 2007;Roseman et al, 1990;Roseman & Smith, 2001;Weiner, 1985Weiner, , 1986, how the attributions combine is yet to be theoretically or empirically delineated. Instead, following other within-person profile-based research (Diefendorff et al, 2019;Slaughter et al, 2021), we offer a few speculations as a "thought exercise" about which profiles might emerge. To guide our exercise, we reviewed studies that qualitatively coded the types of WIF/FIW episodes people experience (Rothstein et al, 2017) or used a qualitative checklist of features involved in WIF/FIW episodes (French, 2017) that could be attributed to our three attribution dimensions.…”
Section: Understanding Profiles Of Wfc Attributionsmentioning
confidence: 99%
“…Action theory also states that the task and social contexts in which an action is situated impose incentives or restrictions on the attainment of goals. University students are at a critical stage of the socialization process [49,50] and gradually learn to recognize the social and employment environment [51,52]. Therefore, How university students perceive the environment outside their universities can critically influence their information-seeking and decision-making behaviors on campus.…”
Section: Moderating Role Of Perceived Environmental Uncertaintymentioning
confidence: 99%